The Effect of Orange Essential Oil Aromatherapy on Sleep Quality in Hospitalized Children - Mahla Salarfard; Bahare Zarei; Zahra Younesi; Asma Nikkhah Bidokhti; Fatemeh Taheri Bojd (Preventive Care in Nursing and Midwifery Journal, 2023)
Background: Sleep disorders are common among hospitalized children. Aromatherapy is one of the interventions with demonstrated effectiveness in improving sleep quality. Objectives: This study was conducted to investigate the effect of orange essential oil inhalation on the sleep quality of hospitalized children. Methods: This semi-experimental study was conducted on 70 children admitted to Valiasr Hospital in Birjand selected by the convenience sampling method and then randomly assigned to two groups of orange essential oil receivers and the control group. In the intervention group, aromatherapy was performed every day for three days in three shifts (10 am, 4 pm, and at the usual bedtime). The researcher completed the BEARS sleep quality questionnaire at the beginning and end of the intervention period. Data analysis was conducted utilizing SPSS version 16 statistical software and chi-square, Mann-Whitney, paired t-test, McNemar, and t-test. Results: There was no statistically significant difference in the demographic characteristics of the children in the two groups (p>0.05). The results showed no significant difference between the two study groups before the intervention regarding different sleep quality domains (p<0.05). After the intervention, there was a significant difference between the two studied groups in the domains of difficulty in falling asleep, waking up during the night, and disturbance in the regularity and duration of sleep (p<0.05), and the intervention group had better scores than the control group. Conclusion: The present demonstrated that inhalation of orange essential oil had a favorable effect on the sleep quality of hospitalized children. This intervention can be introduced and implemented as an effective method to improve the sleep quality of hospitalized children.